PEKANBARU CITY IN INCREASING IVESTATION IN 2018-2019 - Purba, Diyah Pratiwi; ", Wazni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Investment is the main economic activity that can be a prime mover for the economic development of a region, through its broad impact on various efforts to improve the order of economic activities of the people. With investment, there will be a large absorption of labor, which will increase people's income and consumption, so as to increase the regional economic growth in a sustainable manner. Therefore, almost all governments at various levels, one of which is the Investment Service and One Stop Services, is trying to use a strategy to increase investment activities in the city of Pekanbaru.               The purpose of this study is to determine the Strategy of the Investment Service and One Stop Integrated Services in Increasing Investment in Pekanbaru City in 2018-2019. The theory used in this study uses a strategy theory to increase investment according to Mudrajat Kuncoro. This type of research is descriptive qualitative. The data collection technique was carried out by means of face-to-face interviews, mass media and collecting documents related to strategies to increase investment in the regions.               The results show that the strategy of the Pekanbaru City Investment and One Stop Integrated Services Service in increasing investment in 2018-2019 by looking at four aspects of the strategy to increase investment in Pekanbaru City that the Strategy of the One Stop Integrated Services and Investment Service has implemented four aspects, namely image marketing, attraction marketing, infrastructure marketing and people marketing in Pekanbaru City have been done as well as possible for the welfare of the community. However, the results of the strategies and efforts carried out by the Pekanbaru City Investment and One Stop Integrated Services Service have not been optimal or have not succeeded in achieving the target. This is due to the decline in the number of realized foreign investment and also the absence of legal certainty that explains the Spatial Planning and Territory of Riau Province. The strategy carried out by the Pekanbaru City Investment Service and One Stop Integrated Service is only clear from the increasing number of investment realization increases but does not reach the predetermined target so that it does not have a significant impact on the region and society equally. Keywords: Strategy, Government, Investment